Analysis of Factors Inhibiting the Implementation of Fire Hazard Management Policies by the Fire Department of Kupang City - Ernawati DAENG (Journal of Tourism Economics and Policy, 2023)
The reality that occurs in Kupang City is that fire prevention often encounters many obstacles in disaster management so that the output of Regional Regulation Number 24 of 2007 concerning Fire Hazard Management in Kupang City is not implemented effectively. The research method used in this study was a descriptive research method with a qualitative approach, while the informant selection technique used by the researchers in this study was a purposive sampling technique with a total of 76 people. Sources of data in this study were obtained through primary sources and secondary sources, then the data that had been collected was analyzed using data analysis techniques from Creswell (2016: 264-268). The research results show that the dominant factors hindering the implementation of fire prevention policies by the Kupang City Fire Service are; (a) lack of human resources, (b) lack of budget allocation, (c) lack of facilities and infrastructure and (d) outreach.